2020
DOI: 10.1039/c9sc05161a
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the balance: theoretical interrogation of divergent extended heterolytic fragmentations

Abstract: We interrogate a type of heterolytic fragmentation called a ‘divergent fragmentation’ using density functional theory (DFT), natural bond orbital (NBO) analysis, ab initio molecular dynamics (AIMD), and external electric field (EEF) calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 90 publications
(102 reference statements)
0
12
0
Order By: Relevance
“…Recent studies have shown that the internal electric fields along the reaction coordinate in small molecules and enzymes can be an important factor that defines the reaction mechanism and specificity. , To evaluate how the conformational changes involved in HAT can influence the electric field, we performed calculations of the local electric field along the direction of FeO bond in the ferryl complex reactant geometries using TITAN . The results, as shown in Table S4, reveal that in all of the five snapshots used for the WT calculations, the value of the electric field intensity exhibits slight variations as a function of the conformational changes in RCs.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the internal electric fields along the reaction coordinate in small molecules and enzymes can be an important factor that defines the reaction mechanism and specificity. , To evaluate how the conformational changes involved in HAT can influence the electric field, we performed calculations of the local electric field along the direction of FeO bond in the ferryl complex reactant geometries using TITAN . The results, as shown in Table S4, reveal that in all of the five snapshots used for the WT calculations, the value of the electric field intensity exhibits slight variations as a function of the conformational changes in RCs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The energies of the optimized stationary points were recalculated via single-point energy calculation using a larger basis set, def2-TZVP (labeled as B2) for all of the atoms. Electric field calculations were done using TITAN code as in other studies. , Energy decomposition analysis (EDA) , calculations were then carried out on the optimized reactants and transition state geometries to determine the nonbonded interactions of all of the residues.…”
Section: Methodsmentioning
confidence: 99%
“…The Grimme's D3 dispersion correction [49a] is applied in single‐point calculations and the energy profile is presented in the Supporting Information. The external electric fields (EEFs) were applied for the QM/MM calculations using TITAN code [49b] as in other studies [50,51] . The TITAN code was used to generate uniform electric fields on the entire model of the enzyme used for the QM/MM calculations [Figures S5‐S6].…”
Section: Methodsmentioning
confidence: 99%
“…The possibility to control catalysis, regio-, stereo-, and enantioselectivity (as well as the product selectivity in divergent fragmentation reactions) 32 with the help of OEEFs is a very appealing prospect, which could potentially revolutionize chemical synthesis as we know it today. However, an important impediment to the wide-scale adoption of the principles outlined in the previous section is the current difficulty to harness these electrostatic effects in an experimental setting since a meticulous control over the microscopic alignment between the molecule or molecular complex and the oriented field is an essential prerequisite to this end.…”
Section: Practical Implementations Of Oeefsmentioning
confidence: 99%